Mesoscopic Finite Element Method of the Effective Thermal Conductivity of Concrete with Arbitrary Gradation. (27th December 2018) - Huang, Pingming; Zhao, Yu; Niu, Yanwei; Ren, Xiang; Chang, Mingfeng; Sun, Yamin
Abstract : The effective thermal conductivity (ETC) of concrete is the most important parameter in determining the temperature field and thermal stresses. A 2D random polygonal aggregate model and its modified model considering porosity were established in this paper in order to partially replace the experiment for parametric analysis on the ETC of concrete and to save the experiment cost. A mesoscopic finite element method for the ETC of concrete with arbitrary gradation was also proposed. In addition, the influence factors (thermal conductivity of coarse aggregate, cement mortar, and volume fraction of coarse aggregate) of the effective thermal conductivity of concrete were analyzed. The results show that the 2D gradation curve of coarse aggregates is proved to exist, and there is a corresponding relationship between the 2D and 3D gradation curves of coarse aggregates. The effective thermal conductivity of concrete has a positive exponential relationship with the volume fraction of coarse aggregates, a positive logarithm relationship with the thermal conductivity of coarse aggregates, and a positive linear correlation with the thermal conductivity of cement mortar. The most practical way to improve the effective thermal conductivity of concrete is to increase the ETC of the cement mortar, but the most effective way is to replace the aggregate with a material with a high thermal conductivity.